Dynamics of knowledge supply transactions through time in Bulgarian farms - Dimitar Terziev (ARPHA Proceedings)
Knowledge transfer is a driving force for any business. Also, in agriculture. But there is one peculiarity. Here knowledge is individualized, i.e. related to the individual farm. This difference is caused mainly, but not only, by two reasons - a) specific natural conditions (even neighboring fields are not completely similar) and b) personal farmer’s preferences (the right to choose a licensed organic production, or not, for example). The study of the economy of Bulgarian agriculture, conducted in the last two years, allowed us to discover the modes for knowledge supply used by different farmers. Moreover, this study repeated (in a more extended and advanced form) a similar one from 25 years ago, carried out by two members of the current research team. The goal of this article is to discover, analyze and explain changes in the choice of modes for knowledge supply during the past period. The research was conducted in the form of a survey and covered 345 modern Bulgarian farmers. The collected data were processed through: a) comparative quantitative analysis to detect changes over the past 25 years; b) discrete structural analysis to explain the choice of transactional mode; and c) institutional analysis to discover the causes of changes that have occurred. The main conclusion of this part of our research project is normalization. Bulgarian agricultural sector – market, private agents, and public intervention – is moving in a direction similar to those in developed countries.